Luvly Collection / Ahmad Fikri Imran Ahmad Fuad and Nur Fatin Amirah Azmi Kamal - Ahmad Fuad, Ahmad Fikri Imran; Azmi Kamal, Nur Fatin Amirah (2022)
Luvly Collection is a partnership business that offers and selling hijab which are one of essentials in fashions for Muslim women. Luvly Collection was established after seeing the biggest opportunities in Selangor Darul Ehsan when demand for hijab rises. The headquarters of this business located in Putra Height, Selangor and it is owned by Ahmad Fikri Imran Bin Ahmad Fuad and Nur Fatin Amirah Binti Azmi Kamal, a student of Bachelor of Business Administration (Hons) Finance from University Technology Mara (UITM), Kampus Bandaraya Melaka. Luvly Collection serves the demand market by supplying the consumers with needs and wants as many consumers of Muslim women bought hijab at any time they want. Luvly Collection offered the best quality fabrics of hijab such as shawl and bawal which meet the demand market as they are classified as being one of Muslim women’s compulsory and requirement. Luvly Collection is specialized in selling women’s hijab for hijabis in Malaysia through the social media platform such as Facebook page. Online marketing was done in Facebook page as we believe that this is the best marketing strategy because it can reach a wide audience for our target market. Besides, Facebook also can help sellers communicate with their buyers while engaged with their potential customers. Putra Height is a location where people are so busy with their career and daily life as they do not have time to shop for their own. Thus, delivery with postage is our method how the product can be delivered to customers successfully. Moreover, Putra Height is one of location that near with courier service such as DHL Express, ParcelHub, Post Laju, J&T Express and others. Therefore, it easier for customers to purchase our product through online method. As a start-up business, Luvly Collection continue to work and divided task between two partners for the process of business. we set up marketing campaign through Facebook page by providing 13 teasers, 18 graphics and posting for hard sell and soft sell. We utilized the post by follow AIDCA and TISCTA to give more effective engagement.